Reappraisal of the parenchyma-sparing resections for pancreatic neuroendocrine tumors: a Chinese high-volume center experience - Haoqi Zhang; Chunlu Tan; Xubao Liu; Xing Wang (Journal of Pancreatology)
Background:. Parenchyma-sparing resections (PSRs) are increasingly used for small pancreatic neuroendocrine neoplasms (PNENs) to preserve the function of the gland. However, the data are extremely limited due to the rarity of this tumor. Aims:. This study sought to describe the indications, operative technique, short and long-term outcomes of PSRs for PNENs, with a focus on postoperative pancreatic fistula (POPF) and oncologic outcomes. Methods:. From 2008 to 2018, data collected retrospectively from 113 PNENs that underwent PSRs (113/421, 27%) were reviewed. A comparison was conducted of PSRs of PNENs without (group1, n = 101) or with pancreatic transection (group 2, n = 12). Results:. Of the 113 patients, the most common indication for PSRs was insulinoma (80%), followed by NF-PNEN (20%). The majority of lesions were World Health Organization (WHO) G1 grade (80/113, 71%). The mean maximum diameter of the tumors was 19 mm. Patients who underwent PSRs had a low rate of severe postoperative morbidity (7/113, 6%). Pancreatic endocrine and exocrine insufficiency occurred in only 1% and 7% of patients, respectively. And there was no evidence of tumor recurrence after PSRs detected during follow-up. Age was identified as the only independent positive risk factor of POPF in group 1. Patients in group 2 had significantly higher rates of POPF (P = .002), overall morbidity (P = .002), severe morbidity (P = .026), and readmission (P = .004). Conclusions:. PSRs of PNENs appear to be feasible and safe, preserving the endocrine and exocrine function of the gland with no increased risk of recurrence or metastasis. In contrast, PSRs involving transection of the pancreas should be performed more cautiously.